Fine‐scale habitat heterogeneity explains the local distribution of two Amazonian frog species of concern for conservation. (23rd May 2016) - Jorge, Rafael F.; Simões, Pedro I.; Magnusson, William E.; Lima, Albertina P.
Abstract: To test the hypothesis that subtle differences in abiotic requirements can result in almost total spatial segregation, we sampled two species of diurnal frogs, Atelopus spumarius and Allobates sumtuosus, in a primary forest reserve in central Brazilian Amazonia. We conducted visual and acoustic surveys on three occasions over 2 months, in 40 streamside (riparian) plots distributed throughout the reserve's two major drainage basins, using a grid system that covers 64 km 2 . On average, drainages differed in the pH of stream water and the number of connected and isolated streamside pools. Differences in abiotic characteristics of drainages were associated with the spatial distribution of frog species. The occurrence and density of Allobates sumtuosus was negatively related to stream pH and discharge and positively related to the number of isolated pools in plots. The occurrence and density of Atelopus spumarius was associated with streams with high discharge and pH near neutral. These results indicate that although very large reserves will probably contain sufficient landscape heterogeneity to accommodate different species of diurnal frogs, due to strongly patchy distributions, in situ studies using fine‐scale species‐distribution models will be necessary to assess the adequacy of small reserves in Amazonia that cover hundreds of square kilometers or less for the conservation of some anuran species.